Public Services in the Health Sector Based on the Principles of Human-centered Governance in Jeneponto Regency - Meriam, St.; Sangkala, ‎; Nara, Nurdin; Ibrahim, Muh. Akmal (KnE Social Sciences, 2025)
This study was carried out because the critical role of applying the principles of human-centred governance is to improve the quality and access to fairer and more responsive health services in Jeneponto Regency. This study aimed to assess the implementation and supporting and inhibiting factors of these principles in the regional health service system. This study is qualitative and uses a case study method that explores the implementation of the principles of human-centred governance in health services in Jeneponto Regency. Data were collected through in-depth interviews, participatory observations, and documentation studies, and analyzed thematically by using NVivo 12 Plus; the validity of the result was ensured by conducting source triangulation. This study proves that the application of the principles of humancentred governance in health services in Jeneponto Regency has reflected the values of empathy, transparency, accountability, and community participation that have a positive impact on citizen satisfaction and strengthen the relationship between the government and the community. Nonetheless, the actualization of these principles is still constrained by inadequate financing, lack of capacity, unmotivated health workers, poor community involvement, and cumbersome bureaucracy. Thus, local government needs to strengthen the capacity of the resource through strategic efforts, simplify bureaucratic processes, and create a more inclusive and sustainable dialogue space.